Los estudios irlandeses por todo el mundo 2020 - Maureen O’Connor (Estudios Irlandeses, 2021)
The vivacity and resilience of Irish culture have been both challenged and proven by the year 2020, smack in the middle of which I was asked to take over the role of annual international Irish Studies chronicler. The resilience of hard-pressed academics thrown into unprecedented circumstances was also admirable, and I am extremely grateful to those kind souls who agreed to review a sample of some recent publications in Irish Studies for this issue, a sample size I hope to expand the next time around when it is greatly to be hoped we will no longer be working under emergency conditions.